The wage expectations of European college students - Giorgio Brunello; Claudio Lucifora; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2001)
Expected earnings and expected returns to education are seen by labor economists as a major determinant of educational attainment. In spite of this, the empirical knowledge about expectations and their formation is scarce. In this paper we report the results of the first systematic study of the wage expectations of European college students. Our data are based on the replies to the same questionnaire by more than 6000 college students all over Europe. We study the determinants of wage expectations and expected employment probabilities, the variability of these expectations within a field of study and their variation across universities and fields. We also examine the trade-off between expected starting wages and wage growth. In the final section of the paper, we contrast expected returns to education with actual returns estimated from country-specific micro-data. In line with U.S. studies we find that students overestimate returns to education.
Keywords: J30; 330; returns to education; expectations formation; information processing.; Bildungsertrag; Lohn; Erwartungstheorie; Studierende; Bildungsökonomik; Europa